The cloned genome of ground squirrel hepatitis virus is infectious in the animal. - Seeger, C (1984)
The lack of an in vitro infectivity assay for hepatitis B viruses has impeded the analysis of their genetic organization. To examine the feasibility of generating mutant and recombinant viruses after manipulation of cloned viral DNA in vitro, we have tested the infectivity of the cloned genome of ground squirrel hepatitis virus (GSHV) in virus-free Beechey ground squirrels. We demonstrate that cloned GSHV DNA is infectious when injected directly into the liver in the form of trimeric, head-to-tail recombinant clones and recircularized monomeric molecules but not when injected into the portal vein. Infections established in all four recipients of intrahepatic injections of cloned GSHV DNA exhibited the characteristics observed after administration of virus: GSHV surface antigen and viral DNA appeared in the serum 14-22 weeks after inoculation, and both circular and heterogeneous protein-linked forms of viral DNA were found in liver biopsy samples. Furthermore, virus present in the sera of these animals can be transmitted to other ground squirrels. These findings imply that any function of virion proteins in the initiation of infection by hepatitis B viruses can be bypassed with the use of cloned viral DNA and that this animal model is suitable for testing mutant genomes.